Quantifying the influence of soil-rock interfaces on water infiltration rate in karst landscapes - Jiaxin Liu; Ziming Deng; Liding Chen; Yong Huang; Xiaoyu Peng (Geoderma)
Effective water management in karst landscapes is crucial for sustainable land use and ecological conservation. Understanding soil water infiltration, particularly the role of soil-rock interfaces, is vital yet understudied. This study examines the influence of soil-rock interfaces on water infiltration in a karst landscape through in-situ infiltration tests and dye tracer experiments conducted in Southwest China. The research aims to determine how rock outcrops affect soil properties and preferential flow paths, thereby enhancing water infiltration. Soils near rock outcrops (SR) showed significantly lower bulk density, higher porosity, and greater saturated hydraulic conductivity compared to soils farther from outcrops (S), leading to improved infiltration rates. The SR treatment exhibited infiltration rates up to 5.7 times higher than the S treatment, underscoring the role of the soil-rock interface as a preferential infiltration pathway. Dye tracer experiments confirmed the presence of complex infiltration channels at the soil-rock interface, with gaps and macropores facilitating rapid water movement. Quantitative analysis of infiltration channels revealed that the soil-rock gap contributed 60.5 % to total infiltration, loose soil adjacent to rock contributed 19.5 %, and soil away from rock contributed 20 %. These findings have significant implications for water management, vegetation restoration, and soil conservation in karst regions. Leveraging natural soil-rock interfaces can support sustainable land management practices, enhancing water availability and ecosystem resilience.